Service club members of Baguio City : their life meaningfulness and contribution to social transformation - Canave, Grace C. (DMMMSU-OUS : [s.n.], 2016)
Motivation, commitment, and the search for meaning in life are among the potent forces that drive people to set goals and exert optimal effort to realize these goals in order to ultimately achieve satisfaction and contentment in life. This research explore the levels of motivation, commitment and life meaningfulness of service club members in Baguio City in relation to their aspiration to contribute to social change. An analysis of the data gleaned from two separate questionnaires administered to 210 service club members and 225 recipients of the clubs' services was carried out to obtain answers to the problems of the study. As the researcher explored answers to some questions about the motivation, commitment and life meaningfulness of members of service clubs, it is hoped that an awareness of one's role in society as a positive influence may pave the way for higher volunteerism, selfless acts and worthwhile actions towards social transformation. The levels of motivation, commitment, and life meaningfulness of service club members are high. The extent of contribution of the clubs' services to social transformation was perceived as high by the recipients of these services. There is a moderate positive correlation between the members' motivation and life meaningfulness, as well as between their commitment and life meaningfulness. The data from the questionnaires facilitated the conceptualization of a training program which is intended for the service club officers and members.
Bibliography: pages 79-87.
DMMMSU-OUS Library
Keywords: Social work